1989
DOI: 10.1111/j.1365-2133.1989.tb01798.x
|View full text |Cite
|
Sign up to set email alerts
|

Onchodermatitis—correlation between skin disease and parasitic load in an endemic focus in Ecuador

Abstract: Onchocerciasis is a chronic parasitic infection in which infiltration of the skin by microfilariae has been associated with a number of different pathological changes. This survey compared the prevalence of different forms of skin disease in two villages, one of which was located within the endemic zone for onchocerciasis (Zapallo Grande), in a lowland rain forest area of western Ecuador. The commonest skin diseases in both villages were scabies, pyoderma and pityriasis versicolor. In addition changes closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…It has been reported that the frequency of severe dermatological disease is greater in Cayapa compared to blacks living in the same or neighboring villages (Hay et al 1989;Guderian et al 1989). Conversely, the risk of developing chronic eye disease or lymphatic disease from onchocerciasis appears to be greater among the Ecuadorian blacks (Molnea et al 1984).…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that the frequency of severe dermatological disease is greater in Cayapa compared to blacks living in the same or neighboring villages (Hay et al 1989;Guderian et al 1989). Conversely, the risk of developing chronic eye disease or lymphatic disease from onchocerciasis appears to be greater among the Ecuadorian blacks (Molnea et al 1984).…”
Section: Discussionmentioning
confidence: 92%
“…This confirms findings from other studies which did not find an association between intensity of infection with O. volvulus and skin involvement. 1,10,11 Males had higher skin scores than females. This contrasts with findings from Nigeria where females suffered more often and more severely than males from onchocercal skin disease.…”
Section: Discussionmentioning
confidence: 99%
“…Sie ist mit einer verzö-gerten Immunantwort verbunden,die gewöhnlich bei Patienten mit einer geringen Mikrofilarienlast auftritt. Dagegen zeigen Patienten mit einer hohen Mikrofilarienlast keine immunologischen Phä-nomene [8]. Es wurde gezeigt, dass Th2-Zytokine,einschließlich IL-4 und IL-5,bei der Vermittlung einer Reaktion gegen Filarien eine Rolle spielen [9].…”
Section: Der Parasitunclassified